Roles of Marine Macroalgae or Seaweeds and Their Bioactive Compounds in Combating Overweight, Obesity and Diabetes: A Comprehensive Review - Magwaza, S’thandiwe; Islam, Md (Marine drugs, 2023)
Obesity and diabetes are matters of serious concern in the health sector due to their rapid increase in prevalence over the last three decades. Obesity is a severe metabolic problem that results in energy imbalance that is persistent over a long period of time, and it is characterized by insulin resistance, suggesting a strong association with type 2 diabetes (T2D). The available therapies for these diseases have side effects and some still need to be approved by the Food and Drug Administration (FDA), and they are expensive for underdeveloped countries. Hence, the need for natural anti-obesity and anti-diabetic drugs has increased in recent years due to their lower costs and having virtually no or negligible side effects. This review thoroughly examined the anti-obesity and anti-diabetic effects of various marine macroalgae or seaweeds and their bioactive compounds in different experimental settings. According to the findings of this review, seaweeds and their bioactive compounds have been shown to have strong potential to alleviate obesity and diabetes in both in vitro and in vivo or animal-model studies. However, the number of clinical trials in this regard is limited. Hence, further studies investigating the effects of marine algal extracts and their bioactive compounds in clinical settings are required for developing anti-obesity and anti-diabetic medicines with better efficacy but lower or no side effects.